2016
DOI: 10.7205/milmed-d-14-00729
|View full text |Cite
|
Sign up to set email alerts
|

Pilonidal Sinus Disease: A 10-Year Review Reveals Occupational Risk Factors and the Superiority of the Minimal Surgery Trephine Technique

Abstract: Male combatants and female drivers are at higher risk for PSD, whereas officers and administrative personnel are at lower risk. Compared with surgical techniques used at public hospitals, the Army Clinic exclusive use of the Gips minimal surgery technique is associated with fewer sick leave days. Prior surgery for PSD is a positive predictor of recurrence, and these patients warrant secondary prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 19 publications
2
17
0
2
Order By: Relevance
“…In a larger population study, Levinson and colleagues evaluated 3400 patient records in the Israeli military, where the Gips technique is the standard-of-care, and compared outcomes and convalescence times with that of civilian hospitals where there is no standard treatment. This analysis showed sick days to be reduced from 38 days to 25 days with the minimally invasive Gips technique [15].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In a larger population study, Levinson and colleagues evaluated 3400 patient records in the Israeli military, where the Gips technique is the standard-of-care, and compared outcomes and convalescence times with that of civilian hospitals where there is no standard treatment. This analysis showed sick days to be reduced from 38 days to 25 days with the minimally invasive Gips technique [15].…”
Section: Discussionmentioning
confidence: 95%
“…For adolescents, the activity restrictions mandated through the perioperative period and the painful, embarrassing side effects associated with recurrences often lead to a disruption of schooling and social life during an important time in development [3,10]. Minimally invasive approaches such as sinusectomy are associated with minimal social disruption and no activity restrictions [11][12][13][14][15]. Additionally, smaller studies have shown promising results in the application of laser epilation in the primary or secondary management of pilonidal disease [16][17][18][19].…”
mentioning
confidence: 99%
“…Whereas the recurrence rate may seem high, it should be noted that the same method can be used repeatedly with similar results, suggesting that over 90% can be healed with 1-2 operations [17,18,30].…”
Section: Schlüsselwörtermentioning
confidence: 97%
“…Gips popularized this method by using trephines instead of a scalpel for the excision. Results of the Lord and Millar/ Gips technique in over 7000 patients have been described in 9 reports [4,7,11,18,19,22,28,30]. The reported recurrence rates vary from 3 to 28%, with around 25% in the larger studies with longer follow-up.…”
Section: Excision Of Sinuses Through Minimal Separate Excisionsmentioning
confidence: 99%
“…Pilonidal sinus disease was first defined in the literature in 1833 by Herbert Mayo as sinus containing hair (1). Generally, it can be seen at all ages, but is most common in the second and third decades with incidence identified as 26/100.000 (0.026) (2). It is reported to be two times more common in males compared to females (3).…”
Section: Introductionmentioning
confidence: 99%